Predicting and preventing TB breakdowns. (2nd March 2019) - Sibley, R J
Abstract : The UK Government has committed to a strategy of Bovine Tuberculosis eradication, with the stated aim of England becoming TB free by 2038. A review of the progress of the programme was conducted in 2018, (published in October 2018) which made specific and relatively radical changes to the current plan, including changes to governance, technical innovation and better farmer engagement in more effective biosecurity for their cattle herds. This personal opinion on the possible changes to the current programme outlines some radical improvements that could be made to the statutory controls, providing a practical and effective way of implementing the recommendations of the Strategy Review and re-engaging the industry in a robust and effective TB control and eradication strategy.